Histories of Adolescence and Affect: Setting an Agenda - Brickell, Chris (History compass, 2015)
What did adolescence feel like in the past? This article explores the historical relationships between adolescence and affect - feeling, emotion and lived intensities - in order to explore this question. Drawing from a range of examples, it argues for a systematic consideration of the relationships between lived experience and broad historical shifts, in order to ascertain the ways individual affective lives have been shaped by changes in work, forms of leisure and sexual norms. It is then suggested that this systematic approach can be applied to other aspects of young people's lives as well. This is an argument to take feeling seriously and thereby take historical work on histories of adolescence in some new directions.